Assessing women’s empowerment initiatives collaboratively can create positive change - Elias, Marlène; Meinzen-Dick, Ruth S. (CGIAR GENDER Impact Platform, 2021)
Empowerment (https://doi.org/10.1111/1467-7660.00125) is the process by which people gain the ability to make strategic choices in their lives and to act upon them, when they previously could not. It is a complex, intangible, political, context-specic and multidimensional concept that entails changes at multiple (individual, relational, environmental) levels. Even if assessments of empowerment are imperfect, they can contribute to stronger and more accountable programs and policies. Qualitative and quantitative methods can both yield valuable information for assessing empowerment; combining them can yield comprehensive information that cannot be acquired by using any method alone. Understanding empowerment requires research to embrace and address complexity, to unearth the structural barriers that cause inequality. Our review of 15 tools for measuring women’s empowerment shows that all tools explore agency, but most neglect structural causes of disempowerment. Future research on women’s empowerment should seek to better understand the links between empowerment and agriculture, decision-making processes and situations where positive changes in some dimensions of women’s empowerment can cause setbacks in others.